2013
DOI: 10.1590/s1415-790x2013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de álcool e risco para doença coronariana na região metropolitana de São Paulo: uma análise do Projeto GENACIS

Abstract: Objectives: To examine the association between patterns of drinking and coronary heart disease (CHD) risk in a populational sample. Methods: A population-based cross-sectional study carried out from January 2006 to June 2007, in Metropolitan São Paulo, Brazil, in conjunction with the international collaborative GENACIS project (Gender, Alcohol, and Culture: an International Study), with PAHO support. The subjects (1,501; 609 men, 892 women) of this study were residents of randomly chosen households aged 30 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…We note that heavy drinking was a common drinking pattern, similar to what has been found in other recent Brazilian surveys [10] , [16] , [68] [70] . This pattern is specifically frequent in young adults aged between 18–34 years, which exposes them to a range of risk behaviors with adverse short- and long-term consequences, from social and physical problems - such as hangovers or medical illnesses, unprotected sexual activity, alcohol-related car crashes and other unintentional injuries - to increased risk for AUD [16] , [20] , [71] , [72] .…”
Section: Discussionsupporting
confidence: 90%
“…We note that heavy drinking was a common drinking pattern, similar to what has been found in other recent Brazilian surveys [10] , [16] , [68] [70] . This pattern is specifically frequent in young adults aged between 18–34 years, which exposes them to a range of risk behaviors with adverse short- and long-term consequences, from social and physical problems - such as hangovers or medical illnesses, unprotected sexual activity, alcohol-related car crashes and other unintentional injuries - to increased risk for AUD [16] , [20] , [71] , [72] .…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol consumption was assessed using a questionnaire adapted from the Gender, Alcohol and Culture: an International Study (GENACIS study). For the conversion of habitual alcohol consumption to grams of ethanol, 13 g of ethanol were standardized per drink or dose of alcoholic beverage [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effect of alcohol on the heart is a controversial issue. Some studies have reported that alcohol intake can reduce the risk of coronary heart disease, 1 , 2 whereas other studies have reported that alcohol use is associated with increased cardiac morbidity and mortality. 3 5 The results of previous studies on alcohol consumption and heart failure (HF) have also been inconsistent.…”
Section: Introductionmentioning
confidence: 99%